2015
DOI: 10.1007/s13577-015-0126-2
|View full text |Cite
|
Sign up to set email alerts
|

Eribulin upregulates miR-195 expression and downregulates Wnt3a expression in non-basal-like type of triple-negative breast cancer cell MDA-MB-231

Abstract: Triple-negative breast cancer (TNBC), which does not show hormone sensitivity, is a poor prognosis disease without an established targeted treatment, so that establishing a therapeutic target for each subtype is desired. In addition, microRNA (miRNA), a non-cording RNA 19-25 nucleotide-longs in length, is known to be involved in regulating gene expression. We examined miRNA expression after exposure to eribulin, MDA-MB-231 cells, non-basal-like type of TNBC cell lines, and HCC1143 cells, basal-like type of TNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…miR-195-5p is a member of evolutionarily conserved miRNAs termed the miR-15/107 family which has been suggested to have considerable potential in prognostic prediction [3335]. miR-195-5p acts as a tumor suppressor in tumor progression by targeting numerous genes, such as YAP1 in CRC [29], RPS6KB1 in prostate cancer [35], MMP14 in cervical carcinoma [36], and NOTCH2 in osteosarcoma [12].…”
Section: Discussionmentioning
confidence: 99%
“…miR-195-5p is a member of evolutionarily conserved miRNAs termed the miR-15/107 family which has been suggested to have considerable potential in prognostic prediction [3335]. miR-195-5p acts as a tumor suppressor in tumor progression by targeting numerous genes, such as YAP1 in CRC [29], RPS6KB1 in prostate cancer [35], MMP14 in cervical carcinoma [36], and NOTCH2 in osteosarcoma [12].…”
Section: Discussionmentioning
confidence: 99%
“… 166 Triple-negative breast cancer (TNBC) is a heterogeneous subtype of breast cancer characterized by the absence of estrogen, progesterone and HER-2 receptor expression, accounting for approximately 12%–17% of breast cancer cases, having a poor prognosis, and accompanied by a high risk of recurrence. 167 Furuya et al 168 reported that eribulin treatment strongly increases miR-195 levels in a non-basal-like type of TNBC cell line, MDA-MB-231, 168 and miR-195 was reported to downregulate Wnt3a in the same work.…”
Section: Mir-195 In Various Cancersmentioning
confidence: 90%
“…The chemokine signaling pathway mediates chemokines and promotes the chemotaxis, growth, and survival of BC cells [42]. miR-195 suppressed the Wnt signaling pathway, which promotes cell proliferation and the metastasis of TNBC [43]. Han et al reported that the ErbB signaling pathway can be regulated by STAT1 in the tumorigenesis of BC [44].…”
Section: Discussionmentioning
confidence: 99%